Identification of a transcriptional signature found in multiple models of ASD and related disorders - Thudium, Samuel; Palozola, Katherine; L'Her, Éloïse; Korb, Erica

(untitled) (Genome Research, 2022)
Epigenetic regulation plays a critical role in many neurodevelopmental disorders (NDDs), including autism spectrum disorder (ASD). In particular, many such disorders are the result of mutations in genes that encode chromatin-modifying proteins. However, although these disorders share many features, it is unclear whether they also share gene expression disruptions resulting from the aberrant regulation of chromatin. We examined five chromatin modifiers that are all linked to ASD despite their different roles in regulating chromatin. Specifically, we depleted ASH1L, CHD8, CREBBP, EHMT1, and NSD1 in parallel in a highly controlled neuronal culture system. We then identified sets of shared genes, or transcriptional signatures, that are differentially expressed following loss of multiple ASD-linked chromatin modifiers. We examined the functions of genes within the transcriptional signatures and found an enrichment in many neurotransmitter transport genes and activity-dependent genes. In addition, these genes are enriched for specific chromatin features such as bivalent domains that allow for highly dynamic regulation of gene expression. The down-regulated transcriptional signature is also observed within multiple mouse models of NDDs that result in ASD, but not those only associated with intellectual disability. Finally, the down-regulated transcriptional signature can distinguish between control and idiopathic ASD patient iPSC-derived neurons as well as postmortem tissue, demonstrating that this gene set is relevant to the human disorder. This work identifies a transcriptional signature that is found within many neurodevelopmental syndromes, helping to elucidate the link between epigenetic regulation and the underlying cellular mechanisms that result in ASD.